A model-predictive controller for optimal hydro-power utilization of river reservoirs - Linke, H (2010 IEEE International Conference on Control Applications, 2010)
This paper focuses on a two-layer control algorithm for operational management of river barrages, which is based on a model-predictive controller in the upper layer and local controllers at each barrage in the lower layer. The incorporation of hydro-power utilization into the objective function of the predictive controller will be discussed in detail. The process description is based on an efficient numerical schema (Godunov-method) for the full Saint-Venant-equations using a coarse spatial discretization. A simulation study for three barrages of the river Moselle shows the benefits of the suggested approach for a real inflow scenario.